PERENCANAAN RUSUNAMI RUMAH DIFABEL DI SAMARINDA PENEKANAN PADA AKSESIBILITAS - Zakiah Hidayati; Mafazah Noviana; Dina Fitria; Nur Husniah Thamrin; Afita Nur Hayati (Jurnal Kreatif : Desain Produk Industri dan Arsitektur, 2023)
Samarinda has a reasonably high population, with 872 people with disabilities (2021), based on PPDI DPC Samarinda City data. It is challenging for persons with disabilities to own a home. Therefore, a residential building in the form of a disabled-friendly flats that can house a group of people in one structure is required, emphasizing accessibility. This building's design aims to create a flat accessible to disabled people by paying close attention to the building's exterior rustic architecture. This design method involves identifying problems, collecting data and information, and transforming them into ideas or concepts. Accessibility refers to individuals with disabilities. Government-mandated implementation of accessibility features in circulation routes and space elements with standardized dimensions. This accessible Rusunami also gives attention to the exterior of the building's rustic architecture. The use of red brick characterizes the rustic architectural style, concrete finishing with conwood, natural colors of materials, and designs that evoke a natural look.